"Learn from Errors": Post-traumatic growth among second victims - Huanhuan Huang; Tong Liu; Ying Peng; Xingyao Du; Qi Huang; Qinghua Zhao; Mingzhao Xiao; Yetao Luo; Shuangjiang Zheng (BMC, 2024)
Abstract Background Second victims, defined as healthcare providers enduring emotional and psychological distress after patient safety incidents (PSIs). The potential for positive transformation through these experiences is underexplored but is essential for fostering a culture of error learning and enhancing patient care. Objective To explore the level and determinants of post-traumatic growth (PTG), applying the stress process model. Methods The study was conducted at a tertiary general hospital in Chongqing, China. A descriptive, cross-sectional study design was used. A total of 474 s victims were included. An online survey was conducted in November 2021 to assess various factors related to the second victim experience. These factors included PSIs (considered as stressors), coping styles, perceived threats, and social support (acting as mediators), as well as the outcomes of second victim syndrome (SVS) and PTG. Statistical description, correlation analysis, and structural equation modeling were utilized for the data analysis. A p-value ≤ 0.05 was considered to indicate statistical significance. Results The participants reported moderate distress (SVS = 2.84 ± 0.85) and PTG (2.72 ± 0.85). The total effects on SVS of perceived threat, negative coping, social support, positive coping, and PSIs were 0.387, 0.359, -0.355, -0.220, and 0.115, respectively, accounting for 47% of the variation in SVS. The total effects of social support, positive coping, and PSIs on PTG were 0.355, 0.203, and − 0.053, respectively, accounting for 19% of the variation in PTG. Conclusions The study provides novel insights into the complex interplay between perceived threats, coping styles, and social support in facilitating PTG among second victims. By bolstering social support and promoting adaptive coping strategies, the adverse effects of PSIs can be mitigated, transforming them into opportunities for resilience and growth, and offering a fresh perspective on managing PSIs in healthcare settings.